2013
DOI: 10.3109/00016489.2012.747221
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and head and neck squamous cell carcinomas in the South-East of France: prevalence, viral expression, and prognostic implications

Abstract: HPV DNA tested positive in 11.5% of biopsy samples. The HPV prevalence was higher in OSCCs (91.3 vs 27.3, p < 0.0001) and in patients not consuming tobacco (65.2% vs 95.4%, p < 0.0001). The estimated 3-year overall survival rates were 67.0% for HPV-infected patients versus 39.9% for non-infected patients. The high-risk HPV 16 was the most common type detected (65.2%). In 12 of 18 patients exhibiting DNA of high-risk HPV in their tumor tissue, the same viral genome was also present in normal tissue. E6 and E7 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…A study reported an overall HPV prevalence of 46.5% (PCR) in oropharyngeal cancer (53.7%‐tonsil, 30.2%‐base of tongue) for the period 2000–2009 . A second and a third studies reported an HPV prevalence in oropharyngeal cancer of 50% (detection of p16 expression using immunohistochemistry)−65% (PCR) for the period 2007–2009 and of 30.4% for the period 2007–2010 . By contrast, in Sweden, the prevalence of HPV (PCR) in tonsil cancer was evaluated at 93% in 2006–2007 and at 84% in 2004–2007 in base of the tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study reported an overall HPV prevalence of 46.5% (PCR) in oropharyngeal cancer (53.7%‐tonsil, 30.2%‐base of tongue) for the period 2000–2009 . A second and a third studies reported an HPV prevalence in oropharyngeal cancer of 50% (detection of p16 expression using immunohistochemistry)−65% (PCR) for the period 2007–2009 and of 30.4% for the period 2007–2010 . By contrast, in Sweden, the prevalence of HPV (PCR) in tonsil cancer was evaluated at 93% in 2006–2007 and at 84% in 2004–2007 in base of the tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence is steadily decreasing in men and increasing in women . Studies have reported an overall HPV prevalence in oropharyngeal cancer (PCR) comprised between 30.4% and 65.4% . However, the potential impact of HPV infection on incidence trends is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In France, however, HPV infection is found in only 11.5-26% of cases of HNSCC [14]. ERCC1 gene expression and DPD (dihydropyrimidin dehydrogenase) cyclin D1 mutations [15,16] also offer interesting possibilities.…”
Section: Discussionmentioning
confidence: 98%
“…Afin d'obtenir une valeur prédictive de l'efficacité de la chimiothérapie d'induction et d'en diminuer ses toxicités, des études biomoléculaires et génétiques sont en cours : l'infection à papillomavirus humain (HPV) et plus particulièrement la présence de p53 et des ARNm des oncoprotéines E6 et E7 dans les carcinomes épidermoïdes de l'oropharynx apparaissent comme un facteur de bon pronostic, et de bonne réponse à la radiochimiothérapie. Toutefois, cette infection à HPV n'est retrouvée en France que dans 11,5 à 26 % des carcinomes épidermoïdes des VADS [14]. L'expression du gène ERCC1, la recherche de la mutation de la dihydropyrimidine déhydrogénase (DPD) ou de la cycline D1 [15,16] sont également des pistes intéressantes.…”
Section: Discussionunclassified